Existence and uniqueness theorem to a model of bimolecular surface reactions - Ambrazevicius, A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We prove the existence and uniqueness of classical solutions to a coupled system of parabolic and ordinary differential equations in which the latter are determined on the boundary. This system describes the model of bimolecular surface reaction between carbon monoxide and nitrous oxide occurring on supported rhodium in the case of slow desorption of the products.